The Performing Subject in the Space of Technology Through the Virtual, Towards the Real - Causey, M.; Causey, M.; Meehan, E.; Meehan, E.; O'Dwyer, N.; O'Dwyer, N. (Palgrave Studies in Performance and Technology, 2015)
This book reflects on the aftermath of shifts encountered in the maturing of digital culture in areas of critical theory and artistic practices, focusing on the awareness that contemporary subjectivity is one that dwells within both the virtual and the real.